Quality of the digital gp visits and characteristics of the users: retrospective observational study - Sanna Lakoma; Henna Pasanen; Kaisla Lahdensuo; Jaakko Pehkonen; Jutta Viinikainen; Paulus Torkki (Taylor & Francis Group, 2024)
Objectives This study compares the demographics, diagnoses, re-admission rates, sick leaves, and prescribed medications of patients accessing digital general practitioner (GP) visits with those of patients opting for traditional face-to-face appointments in a primary health care setting.Design The study adopted a retrospective analysis of patient record data collected in 2019, comparing visits to a digital primary health center with traditional health center visits.Setting Primary health care.Participants The data encompassed patients who utilized the digital clinic and those who visited public health centers for primary health care services.Main Outcome Measures The study assessed demographics, health diagnoses, prescribed medications, sick leave recommendations, re-admission rates, and differences in costs between digital clinic and face-to-face visits. Secondary outcomes included a comparative analysis of medication categories, resolution rates for health problems, and potential impacts on health care utilization.Results Digital clinic users were typically younger, more educated, and predominantly female compared with health centre users. Digital visits were well-suited for uncomplicated infections, while health centre appointments were associated with a higher prevalence of chronic conditions. Medication patterns differed between the two modalities, with digital clinic users receiving generic over-the-counter drugs and antibiotics, whereas health centre visits commonly involved cardiac and antihypertensive medications. Sick leave recommendations were slightly higher in the digital clinic, but the difference was not significant. Approximately 70% of health problems addressed in the digital clinic were successfully resolved, and the cost of digital visits was about 50,3% of face-to-face appointments.Conclusion Digital health care services offer a cost-efficient alternative for specific health problems, appealing to younger, educated individuals, when compared to the users of public health center, and may enable improvement of cost-effectiveness combined with acceptable demand management and patient segmentation practices. The results highlight the potential benefits of digital clinics, particularly for uncomplicated cases, while also emphasizing the importance of suitable referral mechanisms for in-person consultations.